The Decency of Albert Camus - Principe, Jesus Deogracias Z (Archīum Ateneo, 2020)
This essay explores the place of decency (l’honnêteté) and the decent man (l’honnête homme) in the moral and religious thought of Albert Camus. Focusing primarily on the major fictional works (The Stranger, The Plague, and The Fall), we consider how Camus employs the semantic ambiguity inherent in the notion of being decent, and then develops this into a normative ethical call characterized by responsibility and solidarity. We then explore further how Camus pushes the envelope to make us reflect on whether decency is even possible, both in the sense of addressing the difficulty of taking on moral responsibility, as well as calling into question the decency of the religious mentality. We conclude with reading in Camus not so much a critique as a challenge for the Christian to be true to herself, her ethic, and her faith.